SEMIOTIC ANALYSIS OF CANON CAMERA ADVERTISEMENTS - INDRAWATI, SUSAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Semiotic Analysis, Canon Camera, Advertisement. Advertisement is a medium to deliver message to people with the goal to influence the to use certain products. Semiotics is applied to develop a correlation within element used in an advertisement. In this study, the writer chose the Semiotic analysis of canon camera advertisement as the subject to be analyzed using semiotic study based on Peirce’s theory. Semiotic approach is employed in interpreting the sign, symbol, icon, and index in Canon camera advertisements. This study aims to identify: (1) What kinds of signs are used in the advertisements of Canon Camera based on semioticanalysis?; (2) What is the meaning of each sign in the Canon Camera advertisements?.This study uses qualitative approach by document analysis because the study focuses on identifying sign, interpreting connotation found in Canon Camera advertisements. The writer collected the data by looking at the visual signcontained within the Canon Camera advertisements.The writer found that there were 52 signs in total consisting of 28 icons, 11 indexes and 13 symbols. Most of the connotation meanings of the prited advertisements reflect a certain messages related to  the theme or product that is promoted. Each sign has a very important role to build up expected additional idea of the advertisement. It has function to make clear, support and streng then up a particular message.Finally, the writer suggests the next researchers conduct a study on semiotics by using another from of advertisement. The next researchers are also suggested that theyuse some other theories to gain better understanding about semiotics.